Early structural remodeling and deuterium oxide‐derived protein metabolic responses to eccentric and concentric loading in human skeletal muscle. Issue 11 (12th November 2015) - Franchi, Martino V.; Wilkinson, Daniel J.; Quinlan, Jonathan I.; Mitchell, William K.; Lund, Jonathan N.; Williams, John P.; Reeves, Neil D.; Smith, Kenneth; Atherton, Philip J.; Narici, Marco V.
Abstract: We recently reported that the greatest distinguishing feature between eccentric (ECC) and concentric (CON) muscle loading lays in architectural adaptations: ECC favors increases in fascicle length (Lf), associated with distal vastus lateralis muscle (VL) hypertrophy, and CON increases in pennation angle (PA). Here, we explored the interactions between structural and morphological remodeling, assessed by ultrasound and dual x‐ray absorptiometry (DXA), and long‐term muscle protein synthesis (MPS), evaluated by deuterium oxide (D2 O) tracing technique. Ten young males (23 ± 4 years) performed unilateral resistance exercise training (RET) three times/week for 4 weeks; thus, one‐leg trained concentrically while the contralateral performed ECC exercise only at 80% of either CON or ECC one repetition maximum (1RM). Subjects consumed an initial bolus of D2 O (150 mL), while a 25‐mL dose was thereafter provided every 8 days. Muscle biopsies from VL midbelly (MID) and distal myotendinous junction (MTJ) were collected at 0 and 4‐weeks. MPS was then quantified via GC–pyrolysis–IRMS over the 4‐week training period. Expectedly, ECC and CON RET resulted in similar increases in VL muscle thickness (MT) (7.5% vs. 8.4%, respectively) and thigh lean mass (DXA) (2.3% vs. 3%, respectively), albeit through distinct remodeling: Lf increasing more after ECC (5%) versus CON (2%) and PA increasing after CON (7% vs. 3%). MPS did not differ between contractile modes or biopsy sites (MID‐ECC: 1.42 vs. MID‐CON: 1.4% day −1 ; MTJ‐ECC: 1.38 vs. MTJ‐CON: 1.39% day −1 ). Muscle thickness at MID site increased similarly following ECC and CON RET, reflecting a tendency for a contractile mode‐independent correlation between MPS and MT ( P = 0.07; R 2 = 0.18). We conclude that, unlike MT, distinct structural remodeling responses to ECC or CON are not reflected in MPS; the molecular mechanisms of distinct protein deposition, and/or the role of protein breakdown in mediating these responses remain to be defined. Abstract : In the present study, we explored the interactions between structural and morphological remodeling to eccentric (ECC) and concentric (CON) loading and long‐term muscle protein synthesis (MPS), evaluated by deuterium oxide (D2 O) tracing technique, in humans. ECC and CON RET resulted in similar increases in vastus lateralis muscle thickness, but achieved through distinct architectural remodeling. However, distinct structural remodeling responses to ECC or CON are not reflected in MPS adaptations, suggesting that the molecular mechanisms of distinct contraction‐specific protein deposition are yet to be defined.